Development of ciprofloxacin-loaded polymeric nanoparticles for drug delivery - Kuşat, Kevser; Akgöl, Sinan (Polymer bulletin (Berlin, Germany), 2024)
Studies in which polymeric nanoparticles are used in drug delivery have been one of the subjects of interest in recent years. In this study, histidine-containing polymeric nanoparticles [poly(2-hydroxyethyl methacrylate-co-N-methacryloylamido histidine methyl ester)] were synthesized by surfactant free emulsion polymerization method. Ciprofloxacin was loaded onto the HPCNs surface [CIP-HCPNs]. In the characterization of CIP-HCPNs, scanning electron microscopy, Fourier-infrared analysis, surface area calculations and zeta potential analysis were used. FT-IR data of histidine-free polymeric nanoparticles [HFPNs] and HCPNs demonstrated the successful addition of Histidine to polymeric nanoparticles. SEM images showed that CIP-HCPNs had a size of 131.2 nm with a spherical shape. As a result of Zeta potential studies, the polydispersity index (PDI) of CIP-HCPNs was found to be 0.11, indicating that CIP-HCPNs have a narrowly spaced size distribution. CIP release from CIP-HCNPs showed slow-release properties. At pH 7.4, cumulative CIP release from CIP-HCPNs was 96% (283.35 mg/g) within 6 h, with full drug release achieved at 24 h. It was stated that the drug release kinetic data obtained from CIP release experiments fit the Hixson-Crowell model, and in this model, CIP release from CIP-HCPNs occurred as the square root of the time dependent process based on Fickian diffusion. As a result, CIP-HCNPs developed in the current study, it can be said that it is suitable for drug release.